New frontiers in angle metrology at the PTB. (September 2015) - Geckeler, Ralf D.; Krause, Michael; Just, Andreas; Kranz, Oliver; Bosse, Harald
Highlights: In situ self-calibration of angle encoders without recourse to external standards. Correction of the lateral displacement of angle encoders during self-calibration. Simultaneous calibration of two angle-measuring devices by a shearing technique. Extension of traceable autocollimator calibration from plane to spatial angles. Information on EURAMET Key Comparison on autocollimator calibration. Abstract: An overview of the current status of angle metrology at the Physikalisch-Technische Bundesanstalt (PTB), the national metrology institute of Germany, is provided. We present our novel self-calibration method for the fast and precise in-situ calibration of angle encoders without recourse to external reference standards which relies on a suitable geometric arrangement of multiple heads which read out the radial grating of the encoder. Additional progress has been achieved by adapting an advanced error-separating shearing technique to angle metrology. This technique, by applying defined angle offsets between two angle measuring devices, offers a unique opportunity to cross-calibrate both devices independently of external standards. We also present progress in the development of a novel device for the precise and traceable calibration of spatial angles, the Spatial Angle Autocollimator Calibrator (SAAC). Finally, we report on the status of the first European Association of National Metrology Institutes (EURAMET) Key Comparison on autocollimator calibration.